Editorial: Examining the Complicated Nature of Religious Solidarity - Anja Zalta; Igor Jurekovič (Religions)
As we were sketching out aims for our Special Issue, we decided to focus on societal crisis and the role that religious communities (and religion more broadly) may play in bridging the conflicts of our age [...]